The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2174/138955711796268769
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Properties of Dihydro-Oxadiazine-Based Heterocyclic Derivatives

Abstract: Dihydro-oxadiazine and its derivatives have been demonstrated to be important heterocyclic scaffold platform with bioactive diversity, which present wide activities such as cardiovascular, antitumor, antibacterial, antimicrobial, acricidal, insecticidal, plant-growth regulating, chitin biosynthesis inhibitors and monoamine oxidase inhibition. Versatile features of dihydro-oxadiazine heterocycles have emerged, so the aim of the present paper was to review the recent advances of dihydro-oxadiazine-based heterocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Oxadiazines were found to be ideal drug motifs for Alzheimer′s disease because of their toxicological and pharmacokinetic profiles 16. In our case, we found that the oxadiazine salt 6 could be directly synthesized from 3 aa in one step 15.…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 66%
“…Oxadiazines were found to be ideal drug motifs for Alzheimer′s disease because of their toxicological and pharmacokinetic profiles 16. In our case, we found that the oxadiazine salt 6 could be directly synthesized from 3 aa in one step 15.…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 66%
“…[2][3][4] Among them, the six-membered heterocycle oxadiazines containing one oxygen and two nitrogen atoms have been considered as important skeletons because of their interesting potential in organic and medicinal chemistry. [5][6][7][8][9][10] Unlike their aromatic triazine counterparts, the bivalent character of the oxygen atom endows oxadiazines with an interesting nonaromatic and non-planar geometry which has recently been highlighted and utilized in drug discovery through the concept of "escape from flatland" developed by F. Lovering et al 11,12 Among the different types of oxadiazines classified on the basis of the positions of their heteroatoms, we focused our work on the 3-amino-1,2,4-oxadiazine (AOXD) scaffold (Figure 1). This scaffold is particularly interesting because it presents two stereogenic sp 3 centers; the presence of the bivalent oxygen atom in the α-position of the guanidine moiety affects pKa, strongly decreasing the basicity of the guanidine moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Azaheterocyclic compounds play a vital role in medicinal chemistry owing to the wide range of biological activities of this class of compounds. In this regard, 1,3,4‐oxadiazine derivatives constitute privileged structures that can be frequently found in many biologically active molecules . For example, 2‐(4‐pyridyl)oxadiazine derivatives 1 are antagonists of the effects of tremorine in mice (standard anti‐Parkinson screen), 2‐(4‐biphenylyl)‐4‐(2‐cyanoethyl)‐4 H ‐1,3,4‐oxadiazin‐5(6 H )‐one 2 has been identified as the most efficient monoamine oxidase (MAO) inhibitor, and 3,6‐dimethyl‐4 H (phenyl)‐7‐phenyl‐pyrazolo[4,3‐ e ]‐1,3,4‐oxadiazine‐2,5(2)‐bis‐trimethine cyanine dyes 3 show prominent antibacterial activities (Figure ) …”
Section: Introductionmentioning
confidence: 99%